Impact Of Working Capital Management On Cash Flow And Profitability - Prayoga, Ageng Wahyu; Saputri, Vettyca Diana (Jurnal Ekonomi Islam, Akuntansi, dan Manajemen, 2025)
Effective working capital management plays a crucial role in maintaining smooth company operations, improving cash flow, and supporting the achievement of optimal profitability levels. A common issue faced by companies is the imbalance between current assets and current liabilities, which can lead to financial instability. This study aims to analyze the impact of working capital management on cash flow and profitability in companies. Using financial data from several firms listed on the Indonesia Stock Exchange over a specific period, this research conducts quantitative analysis to measure the relationship between working capital components such as accounts receivable, inventory, and accounts payable on operational cash flow and net profit. The results indicate that efficient working capital management, characterized by rapid turnover of receivables and inventory as well as optimal management of payables, has a significantly positive impact on cash flow and profitability. These findings highlight the importance of working capital strategies in supporting overall financial performance and provide recommendations for management to pay greater attention to working capital policies in financial planning. Therefore, working capital management should not be viewed merely as an administrative function but as a strategic element in creating company value.